The Effect of Various Dipping Times on Protein Level of Keumamah Fish - Jumhuri Jumhuri; Ismail Ismail; sulasmi sulasmi (Universitas Syiah Kuala, 2014)
The aim of this study was to find out protein level of Keumamah fish dipped in water for various times of dipping. This study used 1.5 kg of keumamah fish sample purchased from Peunayong Market Banda Aceh and divided into four treatment groups. P0 was control group without dipping, whereas P1, P2, and P3 were dipped in 100 C of water for 10, 20, and 30 minutes, respectively, with three repetitions each. The average of protein level on P0, P1, P2, and P3 was 13.66, 12.29, 11.8, and 10.56%, respectively. In conclusion, the dipping time affect to decrease keumamah fish protein level.Key words: keumamah, protein level, dipping time